1989
DOI: 10.1083/jcb.109.3.1219
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurements of cytosolic calcium and secretion in single bovine adrenal chromaffin cells by fluorescent imaging of fura-2 in cocultured cells.

Abstract: Abstract. The cytosolic free calcium concentration ([Ca2+]i) and exocytosis of chromaffin granules were measured simultaneously from single, intact bovine adrenal chromaffin cells using a novel technique involving fluorescent imaging of cocultured cells. Chromaflin cell [Ca2+]i was monitored with fura-2. To simultaneously follow catecholamine secretion, the cells were cocultured with fura-2-1oaded NIH-3T3' cells, a cell line chosen because of their irresponsiveness to chromaffin cell secretagogues but their la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
54
2

Year Published

1990
1990
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(66 citation statements)
references
References 34 publications
10
54
2
Order By: Relevance
“…The first examples for TRH and bradykinin stimulation of pituitary cells show a multiphasic progression of exocytosis. This is consistent with previous results obtained with both stimuli (32) (38). All these results are consistent with the postulate Cytosolic free calcium and exocytosis (37).…”
Section: Application Of' the Methods To Neuroblastoma Cellssupporting
confidence: 94%
“…The first examples for TRH and bradykinin stimulation of pituitary cells show a multiphasic progression of exocytosis. This is consistent with previous results obtained with both stimuli (32) (38). All these results are consistent with the postulate Cytosolic free calcium and exocytosis (37).…”
Section: Application Of' the Methods To Neuroblastoma Cellssupporting
confidence: 94%
“…Imaging of intracellular Ca 2+ in single cells was carried out as described in detail elsewhere [3,4]. After differential plating, cells were resuspended in fresh DMEM and seeded onto 22 mm diameter glass coverslips at a density of 1 x 105 cells/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Both of these stimuli lead to Ca 2+ activation of the subplasmalemmal exocytotic sites [2,3]. In contrast, the InsPrmobilizing agonist angiotensin II results in either no secretion or a polarized secretory response as the InsP3-sensitive store [3,5] and the intracellular Ca 2÷ signal [4] are spatially restricted. We have previously shown that, in addition to the InsP3-sensitive store, these cells also possess a caffeinesensitive Ca 2÷ store that is diffusely distributed throughout the cell [5].…”
Section: Introductionmentioning
confidence: 99%
“…After stimulation with nicotine, the chromaffin cells released ATP, which was sensed via a P2 receptor-dependent [Ca 2+ ] i increase by the neighbouring fibroblasts [39]. Extracellular ATP and other nucleotides commonly produce elevations of cytosolic Ca 2+ via activation of either P2Y or P2X receptors [40].…”
Section: Biosensor Cells and Atp Detection Via An Increase Of Cytosolmentioning
confidence: 99%